Profitabilitas, likuiditas dan leverage terhadap corporate social responbility (CSR) pada perusahaan terdaftar di BEI Tahun 2017-2020 - Sularsih, Hermi; As’adi, As’adi (Jurnal Paradigma Ekonomika, 2022)
This study aims to determine the effect of profitability, liquidity and leverage on corporate social responsibility (CSR) in consumer goods industrial sector companies listed on the IDX in 2017-2020. The research data uses data on consumer goods industrial companies listed on the IDX for the 2017-2020 period. The data analysis technique of this research used multiple linear regression with statistical product and service solutions (SPSS) analysis tool. Profitability research results have no significant positive effect on the disclosure of corporate social responsibility as measured using return on assets (ROA), liquidity has a positive effect on the disclosure of corporate social responsibility (CSR) which is measured using the current ratio (CR) while when measured using the quick ratio (QR) Liquidity has a negative effect on the disclosure of corporate social responsibility. Leverage has no significant positive effect on the disclosure of corporate social responsibility as measured using the debt to asset ratio (DAR).